2018
DOI: 10.1111/nyas.13567
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and probiotics: novel immune system modulators in myasthenia gravis?

Abstract: Gut microorganisms (microbiota) live in symbiosis with the host and influence human nutrition, metabolism, physiology, and immune development and function. The microbiota prevents pathogen infection to the host, and in turn the host provides a niche for survival. The alteration of gut bacteria composition (dysbiosis) could contribute to the development of immune-mediated diseases by influencing the immune system activation and driving the pro- and anti-inflammatory responses in order to promote or counteract i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…However, the encouraging results obtained support new studies focusing also on other MG patient subgroups with different clinical presentation and biomarkers. Our results, in agreement with the hypotheses of other authors 16 , suggest the potential interest of therapies aimed at modulating the gut microbiota in the management of MG.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the encouraging results obtained support new studies focusing also on other MG patient subgroups with different clinical presentation and biomarkers. Our results, in agreement with the hypotheses of other authors 16 , suggest the potential interest of therapies aimed at modulating the gut microbiota in the management of MG.…”
Section: Discussionsupporting
confidence: 93%
“…While the precise etiology of MG remains obscure, it is likely that the development of this disease is dependent upon environmental factors in genetic predisposed patients. The commensal bacteria that colonize the gastrointestinal tract may also play a role in the development of the MG; the confirmation of this hypothesis would support new therapeutic strategies 16 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…An increasing number of studies investigating probiotics have been performed in recent years. Lactobacillus is one of the probiotics present in the human intestine, which can improve intestinal microenvironment, regulate immunity and promote nutrient absorption (56)(57)(58)(59). Recent studies have demonstrated that probiotics also have a role in regulating abnormal brain activity (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the biological pathways that were active in the stimulation, a KEGG database was used to map all of the DEGs. Most enriched KEGG pathways were related to metabolism and immune responses, suggesting that Bacillus subtilis stimulus could enhance the metabolism and regulate the immune functions of gDCs, which is similar to the effect of probiotics in mammals [43,44]. It is worth noting that the cytokine–cytokine receptor pathway was significantly enriched during the stimulus.…”
Section: Discussionmentioning
confidence: 99%